Restructuring the Division of Governmental Functions Based on Lean Governance Principles - Firdaus Arifin; Ihsanul Maarif (Journal Equity of Law and Governance, 2024)
The bloated structure of government bureaucracy, characterized by overlapping authorities among ministries, significantly impacts inefficiency in policymaking, resource wastage, and inter-ministerial conflicts, ultimately slowing down public services and disadvantaging society. This study aims to explore the application of lean governance principles as an approach to streamline the bureaucratic structure of state ministries, focusing on waste reduction and workflow optimization. This study employs a normative juridical method with a doctrinal approach to analyze and understand the principles of lean governance in the context of efficient public administration. Data were collected through a literature review encompassing legal literature, scholarly journals, and relevant policy documents. The data analysis was conducted qualitatively using a descriptive-comparative method to assess the alignment of regulatory frameworks governing ministerial authority with the principles of lean governance. The implications of this study include the need for regulatory adjustments to support authority restructuring and enhanced information technology to improve transparency and accountability. Consistent implementation of lean governance is expected to create a more responsive and adaptive government, ultimately fostering greater public trust in the public sector.